Electrochemical performance of yttria‐doped SrCoO3‐δas cathode material for anode‐supported solid oxide fuel cell. Issue 4 (23rd April 2022) - Wang, Yujia; Cheng, Lingyan; Zhang, Qi; Huang, Qi; Sarker, M. D. Abdul Hamid; Jiang, Shanshan; Su, Chao
Abstract: Yttria‐doping strategies of strontium cobaltite (SrCoO3‐δ ) have been systematically investigated as high‐performance cathode materials for anode‐supported solid oxide fuel cells. Sr0.95 Y0.05 CoO3‐δ (SYC), SrCo0.95 Y0.05 O3‐δ (SCY), and Sr0.95 Y0.05 Co0.95 Y0.05 O3‐δ (SYCY) were prepared by the citrate complexation sol–gel method. The crystal structures, oxygen desorption characterizations, electronic conductivities, and electrochemical performances were studied. The research result suggested that yttria doping into the A‐site of SrCoO3‐δ (SYC) exhibited the highest electronic conductivity ( 580 S cm −1 ), and the suppression of the oxygen vacancies results in the poor performance of oxygen reduction reaction (ORR) activity. The yttria doping into the B‐site of SrCoO3‐δ (SCY) inhibits the oxygen desorption related to the Co 3+ to Co 2+ and electronic conductivity. The co‐doping yttria of SrCoO3‐δ (SYCY) shows the lowest area‐specific resistances (0.147 Ω cm 2 at 600°C) and lowest activation energy (103.8 KJ mol −1 ). The ORR processes of SYC, SCY, and SYCY electrodes were analyzed by the distribution of relaxation time (DRT) technique. The I‐V and I‐P performances of SYCY cathode based on the anode‐supported single fuel cell were also being exploited, and the peak power density of this cell is 1005 mW cm −2 at 650°C. The encouraging results suggest that SYCY is a candidate reduction electrode for solid oxide fuel cell.